A systematic review of perspective transformation in humanities: Mezirow’s framework and contemporary issues (2020–2025). - Md Baharudin, Mohd Hakimi; Abd Hamid, Mohd Azhar; Yasin, Yusma Fariza; Yusof, Junaidah (Journal of Islamic, Social, Economics and Development, 2025)
Living with HIV presents complex psychological, social, and existential challenges that go beyond conventional clinical issues. Effective interventions need to adopt a comprehensive and context-based educational approach. However, People Living with HIV (PLHIV) are often viewed as passive recipients in the learning process, with insufficient emphasis on their role as agents of change. This paper proposes a qualitative conceptual framework that explores the potential of Transformative Learning Theory (TLT) as a catalyst in the processes of identity reconstruction and empowerment for PLHIV. Through the synthesis of theory and literature analysis, this framework integrates TLT, Socio-Cultural Theory, Situative Learning, Role Transition Theory, and Bloom's Taxonomy, emphasising holistic learning that encompasses cognitive, emotional, and social dimensions. The framework highlights the importance of past experiences and social context in shaping critical reflection and learning outcomes for PLHIV, shifting their role from passive recipients to active agents of change. This paper also proposes a culturally sensitive adult learning approach to foster self-resilience, reduce stigma, and support ongoing transformation, while also highlighting the potential for future qualitative research through narrative inquiry, phenomenology, and action research.